EFEKTIVITAS AROMATERAPI UNTUK MENURUNKAN NYERI PERSALINAN DI BPM ROSITA KOTA PEKANBARU - Hirza Rahmita (Jurnal Ilmu Kebidanan, 2018)
Pain is a subjective experience that includes complex interactions of physiological, psychosocial, cultural and environmental influences. Labor pain is unique and different in each women and experienced by almost maternity mothers. One of the nonpharmacological methods to reduce pain is aromatherapy which is an ancient healing process using the essence of pure aromatic plants. This study aims to determine the effectiveness of aromatherapy to reduce pain in first stage labor at BPM Rosita Tampan District Pekanbaru city during February-August 2017 by using diffuser and lavender aromatherapy. The research design used was quasy experiment with one group pretest posttest without control design. The sample were 36 respondents who are determined by accidental sampling method. The statistic test used was Wilcoxon Test and obtained p value 0,014 (p <0,05). The results of statistical tests showed before giving aromatherapy the mean value was 5.19 and decreased after aromatherapy treatment was 4.44. So it can be concluded that aromatherapy is effective to reduce pain in the first stage of labor with a mean difference of 0.75. In the future, it is recommended the use of aromatherapy will be further developed with new methods to help reduce the labor pain of maternity mothers